2014
DOI: 10.1159/000363391
|View full text |Cite
|
Sign up to set email alerts
|

The Micronutrient Status of Patients with Phenylketonuria on Dietary Treatment: An Ongoing Challenge

Abstract: Background: In phenylketonuria (PKU), phenylalanine-free L-amino acid supplements are the major source of dietary micronutrients. Methods: Four hundred fifty-two retrospective annual/bi-annual non-fasting blood samples for nutritional markers (plasma zinc, selenium, and serum folate) from 78 subjects aged 1-16 years (median number of blood samples: 6, range 1-14) were analysed over 12 years. Longitudinal blood result data were available for 51 subjects (65%). The dietary intake from supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 12 publications
4
46
0
5
Order By: Relevance
“…This finding is comparable to outcomes in other studies [5,7,8]. However, the clinical relevance of the observed low zinc concentrations is unclear.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding is comparable to outcomes in other studies [5,7,8]. However, the clinical relevance of the observed low zinc concentrations is unclear.…”
Section: Discussionsupporting
confidence: 89%
“…Low plasma selenium serum concentrations, as seen in 46% of our patients, have previously been reported in PKU [7,8]. Plasma selenium is an adequate biomarker for assessing the selenium status in patients on a special diet [30].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…They frequently relax their protein-restricted diet and reduce AAM intake below prescribed amounts. Commonly, patients maintain their habitual dietary practices with a variable degree of natural protein restriction despite relaxed AAM intake, which constitutes a risk for nutritional imbalances and deficiencies [11,12]. In the present prospective cross-sectional study, eating habits, nutritional status, and selected nutritional biomarkers were evaluated in a cohort of adult PKU patients, in relation to their treatment compliance regarding AAM intake.…”
Section: Introductionmentioning
confidence: 99%
“…) that are difficult to consume in adequate amounts with dietary protein restriction (Lammardo et al 2013). Previous studies have shown that the PAH deficiency diet generally meets and even exceeds requirements for most nutrients (Evans et al 2014), but there are no reports of nutrient intake by source: food versus medical food. Phenylalanine restriction and medical food are recommended for life in all patients with PAH deficiency (Singh et al 2014).…”
Section: Introductionmentioning
confidence: 99%